2018
DOI: 10.3389/fonc.2018.00512
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 and Malignancy: A Review

Abstract: In order to determine the role of human herpesvirus 6 (HHV-6) in human disease, several confounding factors, including methods of detection, types of controls, and the ubiquitous nature of the virus, must be considered. This is particularly problematic in the case of cancer, in which rates of detection vary greatly among studies. To determine what part, if any, HHV-6 plays in oncogenesis, a review of the literature was performed. There is evidence that HHV-6 is present in certain types of cancer; however, dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 193 publications
(187 reference statements)
0
43
1
1
Order By: Relevance
“…Still, we cannot rule out a substantial contribution of infected immune cells in pancreas and other tissues. Therefore, in line with current knowledge (reviewed in 16 ), we cannot confirm a link between roseolovirus and tumor development. Especially in matched non-malignant kidney samples, we detected higher roseolovirus positivity without an equally strong signal in the corresponding tumor samples.…”
Section: The Virome Landscape Across 39 Distinct Tumor Typesmentioning
confidence: 51%
“…Still, we cannot rule out a substantial contribution of infected immune cells in pancreas and other tissues. Therefore, in line with current knowledge (reviewed in 16 ), we cannot confirm a link between roseolovirus and tumor development. Especially in matched non-malignant kidney samples, we detected higher roseolovirus positivity without an equally strong signal in the corresponding tumor samples.…”
Section: The Virome Landscape Across 39 Distinct Tumor Typesmentioning
confidence: 51%
“…While infection by HHV-6 is generally asymptomatic, HHV-6B is the etiological factor for exanthema subitum (roseola infantum) [27] which most often produces a non-life-threatening fever and skin rash. Other conditions have been associated to the acute infection or reactivation in immunocompromised individuals, including AIDS encephalopathy, several types of cancer, demyelinating diseases such as multiple sclerosis (MS) and progressive multifocal leukoencephalopathy (PML), chronic fatigue syndrome, febrile seizures, multiple transplant complications, heart, lung and liver diseases, cognitive disfunction, epilepsy, and encephalitis [22,25,[28][29][30][31]. Recently, some studies have implicated the infection by HHV-6 in the pathogenesis of Alzheimer's disease (AD) [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Cytomegalovirus (CMV), a herpes virus with seroprevalence levels between 31.8 and 77.6% in Western Europe (Lachmann et al 2018 ), has been shown to induce chronic antigenic stress (Pawelec and Gouttefangeas 2006 ), which accelerates immunosenescence (Aw et al 2007 ; Solana et al 2012 ). Other herpes viruses, like Epstein-Barr-Virus (EBV), the first identified human oncovirus (Epstein et al 1964 ), herpes simplex virus 1/2 (HSV-1/2) (Bergstrom et al 1990 ; Piacentini et al 2014 ) and human herpesvirus 6 (HHV-6) (Eliassen et al 2018 ) have been linked to the development of cancer and neurological diseases via immunostimulation. Bacterial pathogens, like Helicobacter pylori ( H. pylori ), the causative agent of gastric cancer and ulcer, and Borrelia burgdorferi sensu lato ( B. burgdorferi s.l. )…”
Section: Introductionmentioning
confidence: 99%